While the town slept - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Tim Colter western, 2024)
Deputy U.S. Marshal Tim Colter, an unsung hero of the American West who survived the harsh frontier, fought in the Civil War, and now faces the greatest danger of all: a plot to kill the U.S. President.